2017
DOI: 10.18203/2320-6012.ijrms20173535
|View full text |Cite
|
Sign up to set email alerts
|

The negative correlation between testosterone levels and age in healthy Indonesian men residing in the special capital province of Jakarta, Indonesia

Abstract: Background: Testosterone levels in the circulation determined by production and secretion by Leydig cell in the testes. The action mechanism of testosterone to target cells mediated by sex hormone binding globulin (SHBG). The levels of testosterone and SHBG in circulation determine men's health. The objective in this study to know the relationship between testosterone, SHBG and insulin with age in healthy Indonesian men residing in the special capital province of Jakarta, Indonesia.Methods: This study is a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(55 reference statements)
0
3
0
1
Order By: Relevance
“…38 The results of the study are in line with the results of a study that showed that total testosterone levels were negatively correlated with age. 39 With respect to testosterone levels within the circulation, only free testosterone is available for use by target cells with intermediary sex hormone binding globulin (SHBG). 40,41 It has been demonstrated that SHBG levels in cerebrospinal fluid correlate with decreased cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…38 The results of the study are in line with the results of a study that showed that total testosterone levels were negatively correlated with age. 39 With respect to testosterone levels within the circulation, only free testosterone is available for use by target cells with intermediary sex hormone binding globulin (SHBG). 40,41 It has been demonstrated that SHBG levels in cerebrospinal fluid correlate with decreased cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…(78) The results of a previous study involving 250 healthy men aged 31-60 years showed that total testosterone levels were negatively correlated with increasing age. (79) The results of another study showed that the rate of decline in testosterone production by Leydig cells was about 1% per year. (80) It has been demonstrated that testosterone is important for muscle growth in youth, but testosterone is not essential for maintaining muscle mass in adult male rats.…”
Section: Systematic Review and Metaanalysismentioning
confidence: 99%
“…20 Hasil penelitian terhadap pria Indonesia yang tinggal di Jakarta memperlihatkan bahwa kadar SHBG (nmol/L) mengikuti persamaan Y=48.849-0.328*umur, sedangkan testosterone total (nmol/L) mengikuti persamaan Y=28.827-(0.224*umur), dan kadar testosterone bebas (nmol/L) mengikuti persamaan Y=0.036+(0.001*testosteron total). (23) Testosteron bebas dalam sistem sirkulasi bersifat fungsional (tersedia dan dapat digunakan oleh sel sasaran), sedangkan testosteron dalam bentuk yang terikat bersifat non fungsional (tidak tersedia dan tidak dapat digunakan oleh sel sasaran). Ikatan antara SHBG dan hormon seks steroid dalam aksinya ke sel sasaran ditemukan kemudian setelah teori difusi hormon seks steroid melewati membran sel sasaran.…”
Section: Shbg Memperantarai Aksi Steroid Seksunclassified